Disease burden of asbestos-related diseases in China (1990–2023) based on GBD estimates: A call for stronger labor protection laws - Duo An; Zherui Shi; Chenxiao Zhang; Shichang Song; Lu Wang; Hanchao Li (PLoS ONE, 2026)
Background Asbestos exposure remains a persistent occupational hazard in China, yet updated national estimates of asbestos-related diseases (ARDs) after 2019 are scarce. This study quantified long-term trends and demographic patterns of ARDs from 1990 to 2023 using Global Burden of Disease data and joinpoint regression. Methods We analyzed incidence, prevalence, deaths, and disability-adjusted life years (DALYs) for asbestosis and asbestos-attributable cancers (mesothelioma, tracheal/bronchus/lung cancer, laryngeal cancer, and ovarian cancer). Absolute numbers and age-standardized rates were assessed overall and stratified by sex and age. joinpoint regression identified significant temporal inflection points. Results The absolute burden of ARDs increased continuously from 1990 to 2023. Age-standardized prevalence and incidence rates of asbestosis peaked in 2001, while mortality and DALY rates peaked in 2004. Major turning points for asbestos-attributable cancers occurred around 2010–2011, marking historical peaks followed by declines. A modeled increase in mortality and DALYs was observed from 2020 to 2022 across nearly all ARDs. Males consistently demonstrated higher burdens than females, and older adults (≥65 years) carried the greatest burden, with a secondary mesothelioma peak at 55–59 years in males. Conclusions Although ARD indicators have declined from historical peaks, a statistically modeled increase was observed in 2020–2022, warranting continued public-health attention. These findings aim to provide evidence for clinicians, epidemiologists, and policymakers to strengthen occupational disease prevention, reinforce labor protection laws, and improve asbestos-control policies in China.